Intragovernmental governance in South Africa - An analysis of recent jurisprudence - Andreas SJ Karsten; Marjoné van der Bank (Academicus International Scientific Journal)

(untitled)
In the South African local government domain, municipalities’ ability to execute legislative and executive powers is vested in municipal councils (section 151(2) of the Constitution of the Republic of South Africa, 1996). Given the importance of a municipal council from a functionality perspective, any suspension of executive or legislative decision-making powers can impede the realization of municipal councils’ constitutional purpose, specifically, the objective to provide democratic and accountable governance to local communities. In recent years, local coalition governments have been seen more frequently, partly due to the number of hang councils in South Africa. Governance suffers because of the resulting volatility caused by political standoffs. The departing premise hereto is that the realization of a democratic and accountable government depends on the degree of functionality of every municipal council. Conversely, in councils, volatility can adversely compromise democratic and accountable governance. During recent years, coalition governments in local government have been seen more frequently, partly due to the number of hung councils in South Africa. This article builds on the legal insight provided in the case of the Premier, Gauteng and Others v Democratic Alliance and Others; All Tshwane Councillors who are Members of the Economic Freedom Fighters and Another v Democratic Alliance and Others; African National Congress v Democratic Alliance and Others [2021] ZACC 34. The authors considered using governance mechanisms to provide better support and guidance to ensure the continuation of democratic and accountable government practices, where fractured coalitions have caused governance fallouts in municipal councils.